Modeling And Control Of 2-DOF Underwater Planar Manipulator. - Mat Suboh, Surina; Abd Rahman, Irfan; Arshad, Mohd Rizal; Mahyuddin, Muhammad Nasiruddin (Universiti Sains Malaysia, 2008)
This paper investigates the performance of the fuzzy model reference adaptive control applied on 2-dof underwater planar manipulator (MIMO system). Takagi-Sugeno fuzzification is chosen for the fuzzy system. Proportional-integral update law is used in the adjustment mechanism to obtain a fast parameters adaption.